Family socio-economic status and parental education anxiety: the mediating role of perception of the “double reduction” policy and the moderating role of parental education expectations - Niu, Jinfang; Fang, Jie; Qi, Zhanyong (Frontiers in Psychiatry, 2025)
BackgroundThe “Double Reduction” policy promulgated by the Chinese government in 2021 aims to alleviate parental education anxiety as one of the policy goals, blocking the path of parents’ high participation in their children’s education through intensive out-of-school training and a large number of homework exercises in the past, to comprehensively promote educational equity. However, with the continuous promotion of the policy since its initial introduction, it now faces new controversies. Parents from varying family socio-economic backgrounds exhibit divergent responses to the “Double Reduction” policy, necessitating an examination of parental education anxiety through the lens of family socio-economic status at this juncture.MethodsA survey involving 2,932 parents in China was conducted utilizing the Family Socioeconomic Status Scale, Parents Educational Anxiety Scale, Perception of the “Double Reduction” Policy Scale, and Educational Expectations Scale.ResultsThe findings reveal several key insights: first, educational anxiety is prevalent among parents with an overall medium-to-high intensity level; notably, academic attitude anxiety is most pronounced; second, for each unit increase in a family socio-economic status, there is a corresponding decrease of 0.062 in parental educational anxiety; third, perception of the “Double Reduction” policy effectiveness partially mediates the relationship between family socio-economic status and educational anxiety, while the understanding of the “Double Reduction” policy does not serve as a mediating factor; fourth, parental educational expectations moderated the relationship between perception of the “Double Reduction” policy effectiveness and educational anxiety.DiscussionFour years post-implementation of this policy, and the re-evaluation of the real situation of parents’ education anxiety helps to deeply understand the implementation effect of the “Double Reduction” policy, so as to provide a reference direction for the detailed adjustment of the policy.